TAMAN GEORIMBA MARMAR DAYANG BUNTING LANGKAWI GEOPARK MALAYSIA = DAYANG BUNTING MARBLE GEOFOREST PARK LANGKAWI GEOPARK MALAYSIA - Ibrahim Komoo, Prof, Dato' Dr., 1952-; Norhayati Unjah (Selangor : UNIVERSITI KEBANGSAAN MALAYSIA, 2019)
This coffee table book entitled, Dayang Bunting Marble Geoforest Park: Langkawi Geopark, Malaysia is the third in a series of book on Geoforest Park in Langkawi. The First book, Kilim Karst Geoforest Park: Langkawi Geopark, Malaysia was publish in 2010, while the second book entitled Machinchang Cambrian Geoforest Park: Langkawi Geopark, Malaysia was publish 2015. These coffee table books not only showcase the beautiful landscape of Langkawi Archipelago but are drive from the translational knowledge explored by the researchers from Langkawi Research Centre, since its inceptions. For the first time, Dayang Bunting Marble Geoforest Park is presented through an integrated approach of geological, biological and local cultural heritage. This book is written in two language so that everyone can enjoy it from within and outside the country. From the geological perspective, Pulau Dayang Bunting is formed from limestone, some of which was transformed into marble due to heating from granite intrusion. The ongoing dissolution of this limestone, some of which was transformed into marble due to heating from granite intrusion. The ongoing dissolution of this limestone produced unique tropical island karst landscapes that become a tourist attraction.
Includes index and references pages
Keywords: Langkawi Geopark; Geoparks -- Kedah -- Pualau Langkawi; Geotourism -- Pulau Langkawi; National parks and reserves -- Pulau Langkawi; Biodiversity conservation -- Pulau Langkawi; Tasik Dayang Bunting (Kedah, Malaysia); Government publications -- Malaysia